Chemical composition, antioxidant properties and antimicrobial activity of Mexican propolis - Rodríguez Pérez, Betsabé; Canales Martínez, María Margarita; Penieres Carrillo, José Guillermo; Cruz Sánchez, Tonatiuh Alejandro (Acta Universitaria, 2020)
In Mexico, propolis is offered for its antioxidant activity and antimicrobial activity, so it is necessary to perform its analysis using quality standards. The objective of the present study was to determine the chemical composition of eight propolis from different municipalities of the states Estado de Mexico, Michoacan, Guanajuato, Veracruz, and Puebla. To demonstrate its biological activity, the antioxidant activity was evaluated, and with reference strains of Staphylococcus aureus, Escherichia coli, and Candida albicans the antimicrobial activity was evaluated. The samples from the municipalities of the states Estado de Mexico and Michoacan presented flavonoids, phenols, and terpenes which confer both an increased antioxidant activity and antimicrobial action. Samples from the municipalities of the states of Puebla, Veracruz, and Guanajuato contain terpenes in low quantities, resulting in decreased biological activity and non-compliance with quality specifications. The importance of studying the chemical composition of propolis associated with its biological activity in specific tests was demonstrated.